Interleukin-1 (ɑ&β) Polymorphism and Bevacizumab Response in Neovascular AMD: Jogja Ageing and Genomic AMD Determinant (JAGAD) Study Number 4 - Supanji Supanji; Dewi Fathin Romdhoniyyah; Yola Aulia Alvionita; Kayla Prihatka Salsabila; Septya Olivia Anggraeni; Dewi Megarani Ar-Rosyid; Vera Nurohmah Indrawati; Khairunnissaa' Qonitatun H.; Neilil Muna Mufidana; Dinda Ajeng Anindita; Syania Nursawitri; Sekar Syahriza; Hifdza Faza Felisha; Mohammad Eko Prayogo; Firman Setya Wardhana; Muhammad Bayu Sasongko; Chio Oka (Indonesian Vitreoretinal Society, 2026)
Introduction: Interleukin-1 (IL-1) gene polymorphisms may influence anti-vascular endothelial growth factor (VEGF) treatment response in neovascular age-related macular degeneration (nAMD) by modulating inflammatory pathways. This study evaluated associations between IL-1 (ɑ&β) and anatomical outcomes following intravitreal bevacizumab. Methods: We conducted a multi-center retrospective study involving 84 eyes from 71 nAMD patients at three tertiary hospitals in Yogyakarta, Indonesia. Patients were categorized as responders or non-responders according to whether they achieved a >10% reduction in central macular thickness (CMT) one month post-bevacizumab injection. Peripheral blood samples were collected for DNA extraction and genotyping. Results: Responders demonstrated significantly greater CMT improvement despite having higher baseline values (389.0 µM) compared to non-responders (303.0 µM, p=0.033). At one-month follow-up, responders achieved substantially lower CMT measurements (257.0 µM, p=0.002). The IL-1ɑ risk genotype was not detected in both groups. In addition, the genotype distribution for IL-1ɑ showed no statistical significance difference across age, sex, best corrected visual acuity (BCVA), and CMT. Genetic analysis revealed that carriers of the IL-1β T allele showed a 39% lower probability of being non-responders (OR 0.61; 95% CI 0.32-1.16). The CT and TT genotypes demonstrated even stronger trends, with 34% (OR 0.66; 95% CI 0.15-2.88) and 67% (OR 0.33; 95% CI 0.06-1.72) reduced probabilities of non-response, respectively. However, these associations did not reach statistical significance. Conclusion: Our findings indicate a potential protective effect of the IL-1β -511C/T polymorphism against poor response to bevacizumab therapy, though statistical significance was not achieved. Further investigation with larger sample sizes is necessary to confirm the predictive value of IL-1 genetic variations for anti-VEGF treatment outcomes in nAMD patients.